Pengaruh Stres Terhadap Kadar Hormon Progesteron pada Tikus Wistar Postpartum - , Andria (Jurnal Martenity and Neonatal, 2015)
ASI expenditure on postpartum mother can be influenced by several hormones, including progesterone. Progesterone secretion is closely related to the incidence of stress experienced by the mother postpartum. Increased cortisol in stressful circumstances can reduce the secretion of progesterone as a basic ingredient of these hormones derived from the same raw material, namely cholesterol. The impact of the decrease in the secretion of progesterone in the blood can interfere with the secretion of breast milk. Some studies suggest that progesterone levels increase under stress. This study aims to determine the effect of stress on progesterone levels in Wistar rats postpartum. This type of research in the form of experimental research design with post test only control group design. Number of samples 32 postpartum Wistar rats, the control group consisted of 16 and 16 treated by giving an electric shock stressor. Progesterone hormone levels checked by a method Radio Immuno Assay (RIA) and analyzed by independent t-test. The result showed the average levels of the hormone progesterone in the control group was 21.53 Â± 1.60 ng/ml. While the average levels of the hormone progesterone in the treatment group was 20.23 Â± 1.43 ng/ml. There is a significant effect of stress on levels of progesterone with a value of p = 0.022 (p <0.05). Conclusion: Stress on postpartum rats can significantly reduce levels of the hormone progesterone.